2013
DOI: 10.1093/pcp/pct093
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Cortical Actin Microfilament Patterning in Division Plane Orientation in Plants

Abstract: In land plant cells, division planes are precisely predicted by the microtubule preprophase band and cortical actin microfilament pattern called the actin-depleted zone or actin microfilament twin peaks. However, the function of cortical actin microfilament patterning is not clear. In this study, we report that treatment with the inhibitor 2,3,5-triiodobenzonic acid (TIBA) or jasplakinolide increased the amount of thick actin microfilaments in tobacco BY-2 cells at interphase. However, during the division of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…Several previous studies visualizing F-actin, and/or using actindirected drugs, have suggested that F-actin is not only involved in phragmoplast integrity Smertenko et al, 2011) but also in phragmoplast guidance (Lloyd and Traas, 1988;Sano et al, 2005;Kojo et al, 2013). It is not, however, immediately clear how a role for actin in memorizing the division plane (as it must do in occupying the phragmosomal plane during mitosis) is compatible with the absence of F-actin from the narrow cortical ADZ (Cleary, 1995), to which the phragmoplast appears to be attracted.…”
Section: The Interwoven Roles Of F-actin and Microtubules In Cell DIVmentioning
confidence: 99%
“…Several previous studies visualizing F-actin, and/or using actindirected drugs, have suggested that F-actin is not only involved in phragmoplast integrity Smertenko et al, 2011) but also in phragmoplast guidance (Lloyd and Traas, 1988;Sano et al, 2005;Kojo et al, 2013). It is not, however, immediately clear how a role for actin in memorizing the division plane (as it must do in occupying the phragmosomal plane during mitosis) is compatible with the absence of F-actin from the narrow cortical ADZ (Cleary, 1995), to which the phragmoplast appears to be attracted.…”
Section: The Interwoven Roles Of F-actin and Microtubules In Cell DIVmentioning
confidence: 99%
“…To simultaneously observe microtubules and actin microfilaments in living BY-2 cells, we established BY-YTRF1 cell lines stably expressing yellow fluorescent protein (YFP)-tubulin and tdTomato-ABD2. 15 Using BY-YTRF1 cells, we revealed that altered cortical actin microfilament patterning is strongly correlated with an oblique mitotic spindle orientation at metaphase, suggesting the importance of cortical actin microfilament patterning in regulation of spindle and cell plate orientation. 15 In this study, to further investigate the Precise division plane determination is essential for plant development.…”
mentioning
confidence: 88%
“…15 In approximately one-third of BY-GF11 cells treated with TIBA or jasplakinolide, one or three GFP-ABD2 fluorescence intensity peaks were respectively apparent around the cell center. Aniline blue staining revealed that TIBA and jasplakinolide treatments induced significant increases in oblique cell plate orientations compared with a dimethyl sulfoxide (DMSO) control.…”
mentioning
confidence: 94%
“…Actin disruption with drugs delays cell plate expansion and causes tilted cell plates, 6 but the underlying mechanisms were yet to be discovered. Indeed, actomyosin complex is essential for division via contractile ring in animal and yeast cells.…”
Section: Introductionmentioning
confidence: 99%